Reduced joint reaction and muscle forces with barefoot running - Kim, H. K.; Mei, Q.; Gu, Y.; Mirajalili, A.; Fernandez, J. (Computer Methods in Biomechanics and Biomedical Engineering, 2021)
Barefoot running has been associated with lowered joint loading, but it remains unclear whether the biomechanical benefits are evident after mid-distance running. A musculoskeletal model was adopted for estimating lower limb joint loading for barefoot (n = 10) versus shod (n = 10) 5 km running. The barefoot group reduced peak joint reaction force at the hip and knee, and presented muscle force reductions compared to shod controls with significant group effects and interaction effects (p < .05). These changes were primarily group effects as time point effects were not significant. These findings should be considered when designing barefoot running shoes, running programmes, and injury prevention programmes.